Non-Invasive Respiratory Support Strategy in Adults with Acute Respiratory Failure - Soebekti, Wahyu; Zulfikar, Teuku; Priyanto, Herry (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Patients with acute respiratory failure wil sometimes need invasive mechanical ventilation (IMV). High-demand events such as a pandemic will render the already limited bed in the ICU unavailable for another patient who also needs IMV. Acute respiratory failure can be divided into two categories: hypoxemic respiratory failure and hypercapnic respiratory failure. Non-invasive strategies presently available for treatment of acute respiratory failure are non-invasive ventilation (NIV), continuous positive airway pressure (CPAP), and high flow nasal oxygen (HFNO). Strong evidence has been present for the use of NIV in acute exacerbations of COPD, cardiogenic pulmonary edema, and ARF in immunocompromised patients, while in hypoxemic respiratory failure, there is low to moderate certainty of evidence pointing to the benefit of CPAP and HFNO. Correctly and selectively using these non-invasive strategies can reduce mortality and prevent intubation.